Social Action of Street Children to Sustain Their Life in Pati Regency - Wahyuni, Nur Indah; Prajanti, Sucihatiningsih Dian Wisika; Alimi, Moh Yasir (Universitas Negeri Semarang, 2018)
The number of street children in Pati Regency is always increasing every year. The existence of street children who choose to live free from parental supervision, make them have to work every day in order to survive. This study aims to analyze the social actions of street children to survive in Pati Regency. The focus of this research includes the type of street children's work, work patterns, income amount, and experience during being street children. This research uses qualitative approach. The results showed that street children in Pati Regency chose singing on the streets as their main profession. They sing on 8 – 10 hours in groups or by themselves. Average amount of income Rp 75,000.00 every day. The experience felt by street children is having the freedom to determine life, getting hit by a vehicle while working, and is considered a public bully. The findings of this study are that all actions performed by street children for survival can be categorized into Max Weber's social action theory. The benefits of this research findings can be used as reference for the preparation of strategic steps for the Government in solving the problem of street children.